Distribution and Functional Analysis of Isocitrate Dehydrogenases across Kinetoplastids - Chmelová, Ľubomíra; Záhonová, Kristína; Albanaz, Amanda T S; Hrebenyk, Liudmyla; Horváth, Anton; Yurchenko, Vyacheslav; Škodová-Sveráková, Ingrid (Genome biology and evolution, 2024)
Isocitrate dehydrogenase is an enzyme converting isocitrate to α-ketoglutarate in the canonical tricarboxylic acid (TCA) cycle. There are three different types of isocitrate dehydrogenase documented in eukaryotes. Our study points out the complex evolutionary history of isocitrate dehydrogenases across kinetoplastids, where the common ancestor of Trypanosomatidae and Bodonidae was equipped with two isoforms of the isocitrate dehydrogenase enzyme: the NADP+-dependent isocitrate dehydrogenase 1 with possibly dual localization in the cytosol and mitochondrion and NADP+-dependent mitochondrial isocitrate dehydrogenase 2. In the extant trypanosomatids, isocitrate dehydrogenase 1 is present only in a few species suggesting that it was lost upon separation of Trypanosoma spp. and replaced by the mainly NADP+-dependent cytosolic isocitrate dehydrogenase 3 of bacterial origin in all the derived lineages. In this study, we experimentally demonstrate that the omnipresent isocitrate dehydrogenase 2 has a dual localization in both mitochondrion and cytosol in at least four species that possess only this isoform. The apparent lack of the NAD+-dependent isocitrate dehydrogenase activity in trypanosomatid mitochondrion provides further support to the existence of the noncanonical TCA cycle across trypanosomatids and the bidirectional activity of isocitrate dehydrogenase 3 when operating with NADP+ cofactor instead of NAD+. This observation can be extended to all 17 species analyzed in this study, except for Leishmania mexicana, which showed only low isocitrate dehydrogenase activity in the cytosol. The variability in isocitrate oxidation capacity among species may reflect the distinct metabolic strategies and needs for reduced cofactors in particular environments.
Keywords: NAD; Isocitrate Dehydrogenase; NADP; isocitrátdehydrogenasa; isocitrate dehydrogenase; NAD+; Isocitrates; cofactor preference; isocitráty; NADP+; TCA cycle; Krebs cycle; protein - isoformy; Protein Isoforms